(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
<span style="line-height: 115%; font-family: ’Arial’,’sans-serif’; font-size: 9pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In this paper we introduce a watermarking method which is based on hybrid wavelet transform generated from two orthogonal transforms namely Discrete Kekre Transform and Discrete Cosine transform. As introduced in our previous work, column transform of host and watermark is obtained to make the technique computationally efficient. Watermark is compressed and normalized before embedding to improve imperceptibility of watermarked image. Middle frequency host transform coefficients are used to embed the watermark. Instead of random (row wise) embedment of watermark coefficients into host coefficients, sorting is applied to both coefficients to have a maximum match or minimum difference between them while embedding. Sorting improves the performance of the technique when compared to previous work done without sorting.